THE NATURE OF AND COPING MECHANISMS RELATED TO ENVIRONMENTAL TRANSITIONS IN THE ELDERLY - Sexton, Richard Edmund (The University of Arizona., 1981)
Adjustment to transitional life events and processes of advanced development have emerged as important areas of research. Relatively little attention has been given to the 65+ age group. The present study investigated processes of adjustment to transitional life events by individuals in this group. Sixty-three non-institutionalized males and females volunteered as subjects. Data were collected through face-to-face interviews using a structured questionnaire, a pretested list of transitional life events, an open- and close-ended transition questionnaire, a battery of neuropsychological measures, and several measures of psychological functioning. Results indicated the present sample to be somewhat atypical of the elderly in certain respects--highly educated, quite healthy, and economically secure. A 1 x 6 multivariate analysis of variance and posteriori Hotelling T² tests indicated that while the level of performance on neuropsychological measures of adaptive abilities significantly declined with increasing age, there was also much overlap in performance by the various age groups, particularly among the three oldest cohorts (75 to 85+). Significant intercorrelations were found to exist among measures sensitive to lateralized functions. No significant differences were noted in performance on lateralized measures. Analysis of open- and close-ended descriptions of the nature of transitional life events and adjustment indicated the factors involved to be very complex. Several patterns of adjustment emerged: an immediate tendency to be concerned with practical issues or arrangements, an effort to mitigate the degree of stressful upset through emotional distancing or minimization, consideration of events as distinct from each other to limit the extent of adjustment required, and utilization of immediate and extended social support systems to foster adaptation. Measures of psychosocial functions were not correlated with the number of transitional life events experienced or with the neuropsychological measures employed. However, multiple regression analyses indicated that neuropsychological functioning, level of education, and level of income predicted a significant portion of the variance in ratings of adjustment by three clinical psychologists. Results were discussed in terms of previous research and methodological suggestions for future investigation were presented.